AMPK signaling in osteoarthritis: from mechanisms to targeted therapeutics - Chen, Lin; Hu, Xiu-Hua; Wu, Xin-Yi; Zhang, Xin; Han, Yu-Xin; Liu, Yi; Chen, Guang-Yao; Tao, Qing-Wen (Frontiers in Pharmacology, 2025)
Osteoarthritis (OA) is a common degenerative joint disease characterized by joint pain, swelling, stiffness, and limited mobility. Current treatments primarily offer partial and short-term relief, with concerns about the potential side effects. This underscores the need for safer and more effective therapeutic strategies. AMP-activated protein kinase (AMPK), a key regulator of cellular energy metabolism, plays an essential role in maintaining the homeostasis of articular cartilage, synovium, and subchondral bone. AMPK signaling has been shown to protect joint tissues from damage caused by mechanical stress and inflammatory responses. Studies suggest that modulating AMPK signaling can influence processes such as autophagy, inflammation, and oxidative stress through downstream targets, including the SIRT family and FoxO family. These mechanisms may help reduce cartilage degradation, osteophyte formation, and synovial inflammation. This review provides a systematic overview of the role of AMPK signaling in joint tissues and explores its potential as a therapeutic target for OA, with the aim of informing the development of targeted therapies that may contribute to more effective and safer management of OA symptoms.